Atrial Reentry Tachycardia: Mechanisms and Diagnosis - Almiz, Pavlo O.; Kravchuk, Borys B. (Ukrainian Journal of Cardiovascular Surgery, 2023)
Atrial tachycardia (AT) is a group of arrhythmias that differ in electrophysiological mechanisms and clinical course. There are three main forms of AT: focal AT, macroreentries, and localized reentries also known as “microreentries”. Macroreentries, as a rule, occur in the presence of fibrous changes in the myocardium, for example, in “atrial” cardiomyopathy or as a result of catheter or surgical interventions in the atria. Focal AT can also occur in the absence of structural pathology of the heart. The aim. To analyze modern ideas about electrophysiological mechanisms and diagnosis of atrial reentry tachycardia. In our research we used data from the literature as well as findings of our own previous studies. The work analyzed global data on the distribution of various types of AT. The data of electrocardiographic (ECG) diagnosis, electrophysiological methods of diagnosis and pharmacological tests were also analyzed to determine the mechanism of occurrence and course of AT. The main ECG differences of different types and localizations of AT were determined. The diagnostic value of various stimulation protocols in the differential diagnosis of focal and macro-reentrant AT was also analyzed. Conclusions. Atrial tachycardias with a reentrant mechanism are common in the general population. Differential diagnosis with other types of tachycardia is carried out on the basis of ECG data, the response to adenosine administration, the nature of the response during entrainment, and endocardial, particularly electroanatomical, mapping.